A influência da educação na reeleição dos prefeitos cearenses no ano de 2012 - Lima, Ana Patricia Pierre (2018)
Education is the right of everyone and the duty of the State and the family according to the Federal Constitution of 1988. As the mayors of Brazilian municipalities are the main responsible for public primary education, this research aimed to investigate the relationship between the quality of municipal public education , through IDEB's notes, and the likelihood of re-election of the mayors of the state of Ceará in the 2012 election. The possibility of a selection bias to be present implied the choice of Heckman's (1979) method as a tool for this analysis. The main result is that the quality of education did not affect the probability of re-election of mayors. Another result that drew attention was the impact of per capita expenditures on education only in the last years of the local chief executive's term and may indicate that voters only see policies in the short term. Finally, it is worth mentioning the fact that the greater the number of times municipal accounts were disapproved in the larger TCM will also be the probability of incumbent re-election.